Towards an Aesthetic of Administration: Otto Neurath’s Statistical Materialism and the Art of the Five-Year Plan - Ertl, Tobias (The Nordic Journal of Aesthetics, 2025)
In this essay, I propose to revisit the positive links between socialization, rationalization, and economic planning established in the Marxist debate of the interwar period and its resonances in aesthetic thought and practice. I therefore turn to the work of Otto Neurath, an advocate of Marxism as a form of scientific positivism, fervent defender of centralized planning in the socialization debates of the 1920s, and inventor of a pictorial method of mass education through statistics. I claim that from the perspective of Neurath’s writings, planning and administration can be interpreted as part of a formative process of social freedom. I examine Neurath’s engagement with statistics as a medium of Bildung and highlight the intrinsically aesthetic dimensions of this project. In the second part of the essay, I discuss the importance of statistical imagery and infographics in the context of the Soviet cultural revolution and adjacent European communist art movements of the late 1920s and early 1930s. The aestheticization of statistics and its dissemination into everyday life is a key element of the communist avant-garde’s attempt to collectively organize cultural production beyond the specialized forms of traditional artistic labor. At the historical conjuncture of the first Five-Year Plan (1928–32), the projected synchronization of economic and cultural production resulted—at least on the level of discourse—in a short-lived convergence between an aesthetic of administration and a collectively administered aesthetic practice.